Symptomatic periesophageal vagal nerve injury by different energy sources during atrial fibrillation ablation - Miyazaki, Shinsuke; Kobori, Atsushi; Jo, Hikari; Keida, Takehiko; Yoshitani, Kazuyasu; Mukai, Moe; Sagawa, Yuichiro; Asakawa, Tetsuya; Sato, Eiji; Yamao, Kazuya; Horie, Tomoki; Manita, Mamoru; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Symptomatic gastric hypomotility (SGH) is a rare but major complication of atrial fibrillation (AF) ablation, but data on this are scarce.We compared the clinical course of SGH occurring with different energy sources.Methods: This multicenter study retrospectively collected the characteristics and clinical outcomes of patients with SGH after AF ablation.The data of 93 patients (67.0±11.2 years, 68 men, 52 paroxysmal AF) with SGH after AF ablation were collected from 23 cardiovascular centers. Left atrial (LA) ablation sets included pulmonary vein isolation (PVI) alone, a PVI plus a roof-line, and an LA posterior wall isolation in 42(45.2%), 11(11.8%), and 40(43.0%) patients, respectively. LA ablation was performed by radiofrequency ablation, cryoballoon ablation, or both in 38(40.8%), 38(40.8%), and 17(18.3%) patients, respectively. SGH diagnoses were confirmed at 2(1-4) days post-procedure, and 28(30.1%) patients required rehospitalizations. Fasting was required in 81(92.0%) patients for 4(2.5-5) days; the total hospitalization duration was 11 [7-19.8] days. After conservative treatment, symptoms disappeared in 22.3% of patients at 1 month, 48.9% at 2 months, 57.6% at 3 months, 84.6% at 6 months, and 89.7% at 12 months, however, one patient required surgery after radiofrequency ablation. Symptoms persisted for > 1-year postprocedure in 7 patients. The outcomes were similar regardless of the energy source and LA lesion set.The clinical course of SGH was similar regardless of the energy source. The diagnosis was often delayed, and most recovered within 6 months, yet could persist for over 1 year in 10%.